DIGITAL RESOURCES AS A MEANS OF TEACHING ENVIRONMENTAL MANAGEMENT IN GEOGRAPHY LESSONS - Mussakhan, Ryskul; Aigerim, Abdrakhimova; Borankulova, Dina (Pedagogy and Psychology, 2025)
Some of the outcomes of environmental management activities, while intended to address global issues, have contributed to new environmental challenges. This is particularly concerning for future generations. To address these problems, scientists have emphasized the importance of promoting environmental literacy. However, even before focusing on environmental literacy, it is crucial to foster responsible and sustainable use of natural resources, which are essential to daily life. Passing down this awareness through generations could help prevent future global environmental crises. Therefore, integrating geographical education into strategies for addressing humanity’s challenges is essential. In the study, based on domestic and foreign works, the concepts of teaching environmental management, in particular, information about water sources through digital resources, were analyzed. In addition, in the course of the study of attempts to analyze approaches to teaching the topic «Types of Nature management», research was carried out on tasks in textbooks. The study used descriptive and comparison methods. It is proposed to implement a digital platform in the learning process to enhance the mastery and reinforcement of new lessons, a step that has become increasingly relevant. This platform will incorporate additional tasks and innovative approaches. The study analyzed the platform’s capabilities, including how it facilitates information delivery across subjects, and examined its effectiveness, along with potential barriers to its application. Various studies on teaching approaches in environmental management were also reviewed and compared. The findings can contribute to improving methods and practices in geographic education.